Peningkatan Hasil Belajar Passing Atas Pada Permainan Bola Voli Melalui Variasi Pembelajaran Siswa Kelas XI-SMAN 1 Kampar - Tira Arista; Jufrianis Jufrianis (Pusat Pengembangan Olahraga Universitas Pahlawan, 2026)
The study aims at identifying the learning results of high pass on volleyball among Grade VIII-1 students of SMAN 1 Kampar subdistrict Year 2023/2024 by means of learning variance. The study itself is a Classroom Action Research. When the study was conducted there were two cycles and each cycle consisted of planning, action, observation and reflection. The data sources in the study were the tests to the students in the form of basic high pass technique application in volleyball. Then, the data in the study were gathered by means of assessment toward the learning results of high pass. In analysing the data, the descriptive qualitative technique was implemented with percentage. From the observation, 7 students (21.00%) passed the test while 25 students (79.00%) did not pass the test. Furthermore, in the first cycle 25 students (78.00%) passed the test while the remaining 7 students (22.00%) did not pass the test. In the second cycle, 29 students (90.00%) passed the test while the 3 remaining students (10.00%) did not pass the test.